Photodynamic Therapy With Propolis: Antibacterial Effects on Staphylococcus aureus, Streptococcus mutans and Escherichia coli Analysed by Atomic Force Microscopy: Photodynamic Therapy With Propolis - Fonseca, Alice de Morais Veras; Sampaio, Guilherme Herbet Leite; Araujo, Wládia Pontes; Silva, RaÃ Emanuel; Ribeiro, Fábio de Oliveira Silva; Brito, Manoel Paixão; Araújo, Alyne Rodrigues; Torres, Amanda Azevedo; Pinto, Antonione Santos Bezerra (Journal of Lasers in Medical Sciences, 2020)
Introduction: Photodynamic therapy (PDT) is a process that uses a light source (e.g. laser), oxygen molecules, and a photosensitizing agent. PDT aims to act against pathogens, including those resistant to antimicrobials. The association of PDT with natural drugs, such as Propolis, has not been widely studied. Methods: Therefore, this study aimed to evaluate the antimicrobial effect of PDT in vitro by using Propolis as a photosensitizing agent. For this purpose, the dry Propolis extract was used as a photosensitizer and a low-power laser (Photon Laser III model) was irradiated onto the microwells for 90 seconds. Gram-positive and Gram-negative bacterial strains were used in the tests at a concentration of 5 × 105 CFU/mL. Initially, the antibacterial activity of the photosensitizers without laser action was determined by using a serial microdilution method before the experiment with a laser. After the incubation of the plates in a bacteriological oven, resazurin (0.1%) was added and the minimum inhibitory concentration (MIC) was determined. Alterations in the morphology of the bacteria were analyzed using atomic force microscopy (AFM). Results: Bacteria were sensitive to Propolis with MICs ranging from 13.75 to 0.85 mg/mL, but no susceptibility was observed for methylene blue without laser application. A change was observed for MIC values of Propolis against Staphylococcus aureus after irradiation, which decreased from 1.71 mg/mL to 0.85 mg/mL. However, this behavior was not observed in Escherichia coli, the only gram-negative strain used. In addition, AFM images revealed alterations in the size of one of the bacteria tested. Conclusion: The Propolis is more active against gram-positive bacteria and PDT improved its activity against one of the strains tested.